(Re-)Invention or Revival? The Emperor Augustus and the Re-Introduction of Rituals - Wijeratne, Malka (Sapiens ubique civis, 2023)
The Emperor Augustus promised the revival of the Republic and its values, the revival of Rome’s reputation as a great city and most importantly, he promised and ensured the revival of ancestral rituals. Augustus brought more attention to specific rituals, particularly when he performed them and thus set himself apart from earlier politicians. He also brought attention to rituals that, evidently, had not held a significant position within Roman religious traditions. By placing greater focus on the rituals, Augustus was able to paint himself as the savior of these rituals, thereby setting himself apart from his rivals and gaining the support of the people. This paper intends to look at a handful of examples that describe or depict Augustus actively participating in rituals. It will also explore whether Augustus performed the rituals as they were, or if he ‘re-invented’ them for his own personal gain.